시흥시 보전지역 설정을 위한 조류 서식지 적합성 분석 - 김호걸(Kim, Ho Gul); 박찬(Park, Chan); 이동근(Lee, Dong Kun); 박진한(Park, Jin Han); 배소연(Bae, Soyeon) (국토계획, 2018)
본 연구의 목적은 조류를 대상으로 서식지에 대한 과학적이고 종합적인 평가를 통해 서식 적합성을 평가하고, 이를 바탕으로 시흥시의 보전지역을제안하는 것이다. 특히 야생동물의 서식지를 고려한생태계관리 방법 중 보전지역 설정의 측면에서 접근하기 위하여 야생동물 출현 정보를 바탕으로 서식 적합성 도면을 도출하고, 이를 바탕으로 보전지역을 제안하였다. 본 연구에서는 조류의 서식에 긍정적, 부정적 영향을 미치는 환경인자들을 문헌 조사를 통해 도출한 후, Maximum entropy model을통해 시흥시 비오톱 지도에서 조사된 조류 출현지점 자료를 바탕으로 서식처 적합성을 분석하였다. 그 결과를 통해서 서식처 적합성 분석 결과를 바탕으로 시흥시의 새로운 보전지역을 제안하였다. Siheung-si located in Gyeonggi-do, Republic of Korea is surrounded by green-belt zone used for habitats of wildlife. Recently, policy makers want to adjust green-belt zone to get more development areas. In this context, wildlife animals are in danger because they are losing their habitats. It is necessary to make a proper conservation plan to protect wildlife animals and habitats. Thus, the objective of this study is identifying proper conservation areas for birds by using habitats suitability analysis with Maxent. The habitats suitability analysis is a scientific and objective method to suggest the future conservation area by considering properties of birds’ habitats. The presence data of birds is classified into four bird groups, namely forest birds, water birds, large patch size-required birds, and endangered species, to reflect diverse characteristics of bird communities. The four groups showed different distribution according to different relationship with environmental variables such as biotop types, distance from rivers, and distance from residential areas. We suggested the conservation area considering suitability index (0.8) and 100m buffer zone. The recommended conservation area could be a guideline for establishing conservation plan of Siheung-si. KCI Citation Count: 0